Auto-activity: Decolonization and the Politics of Knowledge in Early Postwar Indonesia, ca.1920-1955 - Sebastiaan Broere (Universitas Gadjah Mada, 2020)
This article presents a history of decolonization and its politics of knowledge by examining rural reconstruction programs in the first decade of Indonesian independence. It traces the roots of Indonesia’s first two agricultural development schemes to late-colonial criticism of state policy. In these criticisms and schemes, “auto-activity” emerged as a key concept. This paper argues that in the writings of planners and politicians, “auto-activity” facilitated the process of decolonization in various ways. The notion of auto-activity affirmed Indonesian know-how over foreign technical assistance; those who developed it would overcome subjective legacies of colonial subjugation; it encouraged the institutionalization of a benevolent state that helped rural communities to help themselves, and would thus contribute to the materialization of a fair and just society. This article concludes that despite these practices of decolonization, programs of “auto-activity” also opened up possibilities to overrule farmers’s individual choices in new ways.